(untitled) (Heritage, 2021)
This crime, introduced in our KZ as an obligation a resulting from the provisions of the Council of Europe Convention on the Protection of Children from Sexual Exploitation and Sexual Abuse, has almost no practical significance in judicial practice. This confirms the past 12 years, since it has existed in the Criminal Code, and although by all parameters, given the „non-existence” of this crime in judicial practice, its decriminalization should be performed, obligations undertailing from the aforementioned Convention do not allow us to do so. But even if we abstrate this fact, we still believe that there are objections that we have pointed to in the work, which the lawmaker has not addressed, and they are in paragraph 1 of this law offence of an essential nature, while in paragraph 2 of this Article, terminological nature. Therefore, in paragraph 1, it is a complaint that allegations of witnessing sexual acts of a criminal character such as rape on the one hand of other punishable sexual acts (adultery with a child, adultery against a powerless person, adultery by abuse of office and illicit sexual activity) on the other hand and especially as a third voluntary sexual relationship. These tentatively stated three types of sex acts cannot be treated in any way together nor can they have the same range of threatened punishment (no matter how much of that range of punishment is). In some future amendments to the KZ, this „anomaly” should be corrected by iciting the child to attend sexual acts such as rape should be incrimination as a more severe form and therefore foresee greater punishment than the existing one. The reason is more than clear and logical, because the presence of a child in the act of rape inevitably creates dangerous and long-lasting consequences for his mental (mental) health. Regarding paragraph 2 of this Constitution, terminologically difficult to subjugation under the notion of forcing a child to attend sex acts. In this sense, corrections should be made that could be in the title of the crime itself, and that correction could be – bringing and forcing the child to attend sex acts.